Biochar and woodchip amendments alter restoration outcomes, microbial processes, and soil moisture in a simulated semi‐arid ecosystem. (28th May 2020) - Fehmi, Jeffrey S.; Rasmussen, Craig; Gallery, Rachel E.
Abstract : Amendments, such as woodchips or biochar, may improve success of arid and semi‐arid wildland revegetation limited by unpredictable and insufficient rainfall as well as low soil water holding capacity. In an 116‐day greenhouse experiment simulating a nearby savannah, response to four amendment treatments (no treatment, incorporated biochar, incorporated woodchips, and surface woodchips) was tested across two field soils (Chiricahua and Hathaway) and four simulated precipitation treatments (100, 80, 60, and 40% of average) in a replicated design. Soil type, amendment treatments, and simulated precipitation all had significant ( p  < 0.01) effects on aboveground biomass. The surface woodchip treatment averaged the highest biomass production of the amendment treatments (489 kg/ha) and the incorporated woodchips had the lowest (298 kg/ha). Aboveground biomass decreased with decreasing precipitation (533, 468, 350, and 216 kg/ha, respectively). Biochar amended soils averaged 5–10% higher volumetric water content than the woodchip amendments and controls through a 28‐day dry down. Microbial nitrogen and phosphorus acquiring activities were higher in Hathaway soils while carbon activities were higher in Chiricahua soils. The surface woodchip treatment resulted in a different species composition than the other amendment and control treatments ( p  < 0.01). None of the amendment treatments ameliorated low precipitation conditions for plants. Contrary to expectations, carbon and phosphorus exoenzyme activities were highest in the lower precipitation treatments (60 and 40%) and nitrogen exoenzyme activities remained high in Hathaway soils regardless of precipitation. Surface application of woodchips increased vegetation as well as carbon and phosphorus exoenzyme activities while incorporating woodchips suppressed vegetation.